Neurofibromatosis type 2 initially presenting as a preauricular mass: a case report - Wei-Che Lan; Yu Aoh; Rui-Yun Chen; Hui-Chi Tien; Chia-Der Lin (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Neurofibromatosis type 2 (NF2) is a rare genetic disease involving multiple tumors of the central and peripheral nervous systems. Most patients with NF2 have bilateral vestibular schwannomas; nonvestibular schwannomas may also develop. While the majority of patients may present with hearing impairment, tinnitus, dizziness and balance disorders, some may present with cutaneous manifestations. We describe the case of a 20-year-old man who initially presented with a solitary subcutaneous painless nodule in the left preauricular area without any other symptoms. He received excisional biopsy for the preauricular mass and the pathologic diagnosis was schwannoma. Magnetic resonance imaging of brain and neck revealed multiple mass lesions over the bilateral cerebellopontine angle cisterns, extending to the bilateral internal auditory canals, bilateral cervical neuroforamens, cervical and upper thoracic spinal canals, and left posterior neck. The patient was diagnosed with NF2 according to the clinical criteria. He underwent gamma knife stereotactic radiosurgery for bilateral vestibular schwannomas and is now under regular monitoring. Conclusion NF2 patients may present with an isolated solitary cutaneous schwannoma with no other associated clinical findings. Further assessment is thus warranted in young patients presenting with a peripheral schwannoma despite absence of other clinical findings.